Modeling the Influence of Treatment Accessibility and Treatment Compliance on the Dynamics of HIV/AIDS (Journal of Nonlinear Modeling and Analysis, 2025)
The invention of highly active antiretroviral treatment (HAART)revolutionalized the treatment of HIV and brought hope to millions of individuals living with the virus. However, the eradication of HIV has proveddifficult owing to many factors including accessibility and treatment compliance, particularly among many individuals in low income countries. Thus, wedeveloped a model in terms of a system of nonlinear ordinary differential equations to assess the influence of inaccessibility of treatment and noncompliancewith treatment guidelines by the HIV infectives who are aware of their statuson the spread of HIV. The model was studied qualitatively and quantitativelyusing the theory of reproductive ratio and the software Maple respectively.The results of the analysis showed that early detection, treatment accessibilityand treatment compliance by the majority of the infectives who know theirstatus are crucial to the minimization of HIV incidence and prevalence.
Keywords: Isolation; incubation period; asymptomatic; symptomatic; equilibria.